Managing knowledge practice in Malaysia's E-government implementation - Mohamed, Norshidah (ICT Research and Development Programme, INTAN, Bukit Kiara, 2009)
The final stage of e-government implementation is transformation. This is marked by a re-defines structure in public organizations' delivery or services to citizens and constituents through a single point of contact. The Internet has been viewed as one particular mechanism to break down bureaucratic barriers between agencies. A common misconception, however, is that technology alone could do all the wonders in transformation. Technology should be viewed as a tool that supports effective delivery of services. Using appropriate technology and managing knowledge effectively is a capability for public organizations to make substantial progress towards reaching transformation. This paper reports the results of a study on public officers, perceptions of managing explicit and tacit knowledge practices in Malaysia's e-government systems implementation as a first step in the knowledge management journey. A comparison on the perceptions amongst each e-government system implemented is provided. Implications that arise from this study are also discussed.